Evaluation of serum ghrelin levels in patients with vitiligo - Demir, Betül; Uçak, Haydar; Çiçek, Demet; Erden, Ilker; Dertlio?lu, Selma; Aydin, Süleyman; Halisdemir, Nurhan (OrtadogÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2014)
Objective: There are several publications about vitiligo being related to metabolic disturbances such as insulin resistance, lipid abnormalities, and metabolic syndrome. Plasma ghrelin levels were found to be low in obese patients and it is accepted to be one of important findings of metabolic syndrome such as hyperinsulinemia and insulin resistance. The current study aimed to investigate change in serum ghrelin levels in patients with vitiligo. Material and Methods: A total of 30 patients presenting with vitiligo and 30 control subjects participated in this study. Fasting blood glucose, serum lipids, insulin, C-peptide and thyroid function tests were measured. The homeostasis model assessment of insulin resistance (HOMA-IR) was used to calculate insulin resistance. Ghrelin levels were determined by enzyme-linked immunosorbent assay (ELISA) according to the manufacturer's protocol. Results: The mean serum ghrelin levels in the vitiligo patient group was 45.27±16.12 pg/mL and was statistically significantly higher in the control group 35.89±19.37 pg/mL, (p=0.04). The mean serum ghrelin level in the patients with insulin resistance 31.65±16.69 pg/mL was compared to the patient without insulin resistance 43.55±17.99 pg/mL and found statistically significant lower (p=0.02). Conclusion: In conclusion, the researchers found that ghrelin levels in patients with vitiligo were significantly high compared with controls and the researchers could not correlate this condition with serum glucose levels and body mass index. This increase in serum ghrelin levels in patients with vitiligo might be related to oxidative stress. Copyright © 2014 by Türkiye Klinikleri.
Vitiligolu hastalarda serum grelin seviyesinin de?erlendirilmesi
Keywords: Ghrelin; Insulin resistance; Vitiligo